STRATEGY OF THE SCHOOL PRINCIPLE IN INCREASING THE COMPETENCE OF EARLY CHILDREN'S EDUCATION TEACHERS - Falah, M. Rizqi Fajrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the principal's strategy in improving teacher competence in PAUD Raudlatul Hasaniyah Sambirampak Kidull and the impact of the principal's strategy in improving teacher competence in PAUD Raudlatul Hasaniyah Sambirampak Kidull. The research method uses a qualitative type of research and a case study approach. The subject of the study was class A with 25 children, data collection techniques with snowball sampling, and the data sources used were primary and secondary. Data collection techniques through interviews, observation and documentation. Data analysis using miles Huberman analysis consisting of data reduction, data display and concluding. The study results obtained that the principal's strategy for improving the competence of teachers at PAUD Raudlatul Hasaniyah Sambirampak KidullKotaanyarProbolinggo includes: Workshops, Supervision and Training. Meanwhile, the impact of the principal's strategy in improving teacher competence at PAUD Raudlatul Hasaniyah Sambirampak Kidull is the increase in teacher creativity, teacher professionalism and adequate facilities.